Análise de SNPs relacionados com doenças cardiovasculares em indivíduos com ancestralidade africana e europeia - Lintz, Hugo Santos (2024)
Cardiovascular diseases (CVD) are the most common type of non-communicable disease in the world, responsible for more than 17 million deaths in 2017, of which more than three-quarters occurred in low and middle-income countries, in addition to being complex and heterogeneous, involving the interaction of genetic, epigenetic and environmental factors. Regarding CVD, 5,3% of the adult population in Brazil has received a medical diagnosis of some cardiac condition, totaling more than 8 million people. The modern human species, characterized as Homo sapiens sapiens, originated from populations located in sub-Saharan Africa 200 thousand years ago. Even though their origins came from the same region, years of geographic isolation allowed genetic differentiation between populations. Approaches based on genetic ancestry use genetic markers with large differences in allele frequency between ancestral groups, called ancestry-informative markers. The most widely used are based on Single Nucleotide Polymorphisms (SNPs), which demonstrate superior ability to predict biogeographic origin. The identification of SNPs associated with the risk for the development of more complex diseases is an important objective within modern genetic studies. Each genetic variant is valuable to indicate a gene or pathway of biological relevance to the disorder. Thus, the present study aims to analyze SNPs related to cardiovascular diseases in individuals with African and European ancestries in the Brazilian population. The results show that traits such as hypertension and cardiomyopathies are more associated with African and European ancestry, respectively, while others are more evenly distributed between the two populations.